2016
DOI: 10.1007/s00436-016-5249-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity of cercarial clones of Himasthla elongata (Trematoda, Echinostomatidae) determined with AFLP technique

Abstract: The aim of this study was to reveal genomic diversity formed during parthenogenetic reproduction of rediae of the trematode Himasthla elongata in its molluskan host Littorina littorea. We applied amplification fragment length polymorphism (AFLP) to determine the genomic diversity of individual cercariae within the clone, that is, the infrapopulation of parthenogenetic progeny in a single molluskan host. The level of genomic diversity of particular cercariae isolates from a single clone, detected with EcoR1/Mse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moreover, the periwinkles in the studied population were previously shown to bear single-miracidium infection. Individual cercariae amplified fragment length polymorphism (AFLP) analysis showed that larvae cluster according to their origin – that is, according to the mollusc they were extracted from (Galaktionov et al ., 2016). So, in our case, multiple infection of the host by H. elongata miracidia cannot explain variation of cercarial photoreactions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the periwinkles in the studied population were previously shown to bear single-miracidium infection. Individual cercariae amplified fragment length polymorphism (AFLP) analysis showed that larvae cluster according to their origin – that is, according to the mollusc they were extracted from (Galaktionov et al ., 2016). So, in our case, multiple infection of the host by H. elongata miracidia cannot explain variation of cercarial photoreactions.…”
Section: Resultsmentioning
confidence: 99%
“…Several other systems with low PI and, hence, likely single miracidium infection provide evidence of genetic heterogeneity in cercariae produced within one snail individual (Khalturin et al ., 2000; Semyenova et al, 2005; Solovyeva et al ., 2013; Galaktionov et al , 2014). Intraclonal polymorphism in cercariae apparently emerges during their embryogenesis, because it is detected not just among cercariae emitted by one mollusc, but also among the offspring of one redia (Galaktionov et al , 2016) or sporocyst (Korsunenko et al , 2013). We suppose that genetic diversity in the absence of meiosis is assumed to be guided by several possible mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-and interclonal variability in infectivity rates and longevity [28], as well as in responses to light and gravity, have been observed in the larvae [29]. Clonal polymorphism in cercariae has been previously described [30], but the source of this phenomenon is unclear. In this work, we analysed the repetitive elements in the primary sequence of the H. elongata genome and in transcriptome data, identified clonal polymorphism in separate cercariae by using simplified amplified fragment length polymorphism (SAFLP), and annotated particular SAFLP fragments.…”
Section: Introductionmentioning
confidence: 99%